Simulation of a waveguide turnstile connection with a square waveguide output for the incoherent scatter radar antenna - Чепурный, Я.Н.; Черняев, С.В.; Скляров, И.Б. (Radiotekhnika, 2012)
The computer simulation of the turnstile connection with a square waveguide output has been carried out. The matching unit dimensions have been optimized, and the main characteristics have been obtained. The use of the connection as a polarizer and antenna switch for incoherent scatter radar is proposed.